Evaluation of the antimicrobial function of Ginkgo biloba exocarp extract against clinical bacteria and its effect on Staphylococcus haemolyticus by disrupting biofilms. (15th November 2022) - Wang, Cong; Wei, Peng-Wei; Song, Chao-Rong; Wang, Xu; Zhu, Gao-Feng; Yang, Yong-Xin; Xu, Guo-Bo; Hu, Zu-Quan; Tang, Lei; Liu, Hong-Mei; Wang, Bing
Abstract: Ethnopharmacological relevance: The fruit of Ginkgo biloba L. (Ginkgo nuts) has been used for a long time as a critical Chinese medicine material to treat cough and asthma, as well as a disinfectant. Similar records were written in the Compendium of Materia Medica (Ben Cao Gang Mu, pinyin in Chinese) and Sheng Nong's herbal classic (Shen Nong Ben Cao Jing, pinyin in Chinese). Recent research has shown that Ginkgo biloba exocarp extract (GBEE) has the functions of unblocking blood vessels and improving brain function, as well as antitumour activity and antibacterial activity. GBEE was shown to inhibit methicillin-resistant Staphylococcus aureus (MRSA) biofilm formation as a traditional Chinese herb in our previous report in this journal. Aim of the stud: yThe antibiotic resistance of clinical bacteria has recently become increasingly serious. Thus, this study aimed to investigate the Ginkgo biloba exocarp extract (GBEE) antibacterial lineage, as well as its effect and mechanism on S. haemolyticus biofilms. This study will provide a new perspective on clinical multidrug resistant (MDR) treatment with ethnopharmacology herbs. Methods: The microbroth dilution assay was carried out to measure the antibacterial effect of GBEE on 13 types of clinical bacteria. Bacterial growth curves with or without GBEE treatment were drawn at different time points. The potential targets of GBEE against S. haemolyticus were screened by transcriptome sequencing. The effects of GBEE on bacterial biofilm formation and mature biofilm disruption were determined by crystal violet staining and scanning electron microscopy. The metabolic activity of bacteria inside the biofilm was assessed by colony-forming unit (CFU) counting and (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2HY-tetrazolium bromide (MTT) assay. Quantitative polymerase chain reaction (qPCR) was used to measure the gene expression profile of GBEE on S. haemolyticus biofilm-related factors. Results: The results showed that GBEE has bacteriostatic effects on 3 g-positive (G + ) and 2 g-negative (G - ) bacteria among 13 species of clinical bacteria. The antibacterial effect of GBEE supernatant liquid was stronger than the antibacterial effect of GBEE supernviaould- like liquid. GBEE supernatant liquid inhibited the growth of S. epidermidis, S. haemolyticus, and E. faecium at shallow concentrations with minimum inhibitory concentrations (MICs) of 2 μg/ml, 4 μg/ml and 8 μg/ml, respectively. Genes involved in quorum sensing, two-component systems, folate biosynthesis, and ATP-binding cassette (ABC) transporters were differentially expressed in GBEE-treated groups compared with controls. Crystal violet, scanning electron microscopy (SEM) and MTT assays showed that GBEE suppressed S. haemolyticus biofilm formation in a dose-dependent manner. Moreover, GBEE supernatant liquid downregulated cidA, cidB and atl, which are involved in cell lysis and extracellular DNA (eDNA) release, as well as downregulated the cbp, ebp and fbp participation in encoding cell-surface binding proteins. Conclusions: GBEE has an excellent antibacterial effect on gram-positive bacteria and also inhibits the growth of gram-negative bacteria, such as A. baumannii (carbapenem-resistant Acinetobacter baumannii ) CRABA and S. maltophilia. GBEE inhibits the biofilm formation of S. haemolyticus by altering the regulation and biofilm material-related genes, including the release of eDNA and cell-surface binding proteins. Graphical abstract: Model depicting GBEE inhibition of S. haemolyticus biofilm formation. GBEE interferes with the formation of S. haemolyticus biofilms by affecting genes involved in the quorum sensing (QS) system ( agrB, lepB ) and the two-component system ( lytS, lytR ). GBEE hinders the formation of S. haemolyticus biofilms by regulating the genes that release eDNA ( cidA, cidB, atl ) and genes encoding cell-surface binding proteins ( cbp, ebp, fbp ). Image 1